PERSEPSI, SOSIAL EKONOMI, FAKTOR BUDAYA DENGAN PEMILIHAN PENOLONG PERSALINAN DI DESA LAMBUSANGO KABUPATEN BUTON - Taswin Taswin; Zaltia Amun (Politeknik Kesehatan Kemenkes Mamuju, 2016)
Selection of birth attendants is a service form towards labor of a mother who is done by health workers such as doctor and midwife or a soothsayer. This study aimed to find out the correlation between perception, social-economy, culture and selection of birth attendants at lambusango chief in kapontori subdistrict, Buton regency. Research design was the analytic method with the cross-sectional approach. Total sample was 67 respondents. The result of study was analyzed by using Chi square with p value < 0.05. This study found that there was a correlation between perception and selection of birth attendants (p value = 0.003<0.05), there was a correlation between culture and selection of birth attendants (p value = 0.003<0,05) and there was no correlation between social economy and selection of birth attendants (p value = 0.690>0.05). The conclusion of study is perception and culture variable have a correlation with selection of the attendants while social economy has no correlation.